Antifungal potential of Cyanobacterium Desertifilum dzianense against collar rot pathogen in Chickpea - Lakshmi Singh; Aparna Nayak; Maheswari Behera; Gangadhar Sethi; Saleh S. Alheswairini; Jayanthi Barasarathi; Riyaz Sayyed; Deepak Kumar Behera; Varanasi Adarsh (Scientific Reports)
Abstract Collar rot, caused by Agroathelia rolfsii, is a devastating soil-borne disease affecting Cicer arietinum L (chickpea) leading to significant agricultural productivity losses. This study investigates the antifungal potential of the cyanobacterium Desertifilum dzianense, isolated from monument stone crusts in Odisha, India, as a natural biocontrol agent against A. rolfsii. Phytochemical screening of crude extracts revealed the presence of bioactive secondary metabolites, including alkaloids and phenolic compounds. The methanolic extract demonstrated the highest antifungal activity, with significant inhibition of A. rolfsii growth in agar well diffusion assays. Thin Layer Chromatography (TLC) analysis identified active fractions, which were further characterized by UV-Vis and FTIR spectroscopy, confirming the presence of alkaloids as the primary antifungal compounds. The bioautography assay validated the antifungal efficacy of the purified fractions. These results support that D. dzianense have strong antifungal potency and can be used as eco-friendly biocontrol agent to control collar rot in chickpea cultivation. However, field trials and cytotoxicity assessment can reflect the safety and efficacy of this biocontrol system.